The Influence of Political Education and Democracy for the Young Generation on the Level of Participation in the Implementation of General Elections - Rohmat, Rohmat; Syariefuddin, Iqbal; Holish, Amarru Muftie (Law Research Review Quarterly, 2018)
Political education is a systematic and deliberate educational effort to form individuals who are politically aware and capable of becoming political actors who can be morally responsible in realizing the political goals themselves. To support this, the role of youth is an important key in organizing democratic life in Indonesia. In article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia it is expressly stated that the sovereignty of the state is in the hands of the people and youth are part of it. As affirmed in Law Number 40 of 2009 concerning Youth emphasizes that the young generation has the position and the main role in realizing the life of a democratic Indonesian nation. This shows that the people are an important part of national and state life. Youth plays an active role as a moral force, social control, and agent of change in all aspects of national development. The Spirit of Youth Law which saves youth in every aspect becomes an important part, but in its implementation it does not always run properly. Sociological facts show that not fully Indonesian youth are aware of their important role as a major part in the taking part of organizing this country. The youth have a moral obligation in realizing a generation of political literacy and have a character that is in accordance with the noble values ​​of the Indonesian people in developing the country's democracy.